2021
DOI: 10.3390/ani11020440
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of GnRH–Loaded Chitosan Nanoparticles for Inducing LH Secretion and Fertile Ovulations in Protocols for Artificial Insemination in Rabbit Does

Abstract: Gonadotropin-releasing hormone (GnRH)–loaded chitosan nanoparticles (GnRH–ChNPs) were used at different doses and routes of administration to induce ovulation in rabbits as an attempt to improve artificial insemination (AI) procedures and outcomes. In this study, the characteristics (size, polydispersity, loading efficiency, and zeta-potential) of GnRH–ChNPs and the GnRH release pattern were determined in an in vitro study. A first in vivo study assessed the pituitary and ovarian response to different GnRH–ChN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 30 publications
6
32
1
1
Order By: Relevance
“…The alginate nanocomposites have recently received much attention as drug delivery nanoparticles [14]. It has efficient biodegradability, biocompatibility, and mucoadhesiveness nature making them superior natural polymers that are ready to use as a drug delivery nanocomposite for target tissue [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The alginate nanocomposites have recently received much attention as drug delivery nanoparticles [14]. It has efficient biodegradability, biocompatibility, and mucoadhesiveness nature making them superior natural polymers that are ready to use as a drug delivery nanocomposite for target tissue [24].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, due to the low bioavailability of bromocriptine [12], there is a great demand for more convenient, effective, and safe ways for drug delivery. Nano-drug delivery systems could be a promising alternative to extend the half-life time of active principles and to sustain its delivery to the target sites [12][13][14][15][16]. It was found that nanocomposites reduced the dose of the drug and the desired biological activity could be obtained with minimal side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Particle size and size distribution (Polydispersity index, PdI) of the free alginate-CaCl 2 nanoparticles and encapsulated synbiotic (Moringa and yeast cells) were measured using a Zetasizer instrument (Malvern Instruments, Malvern, UK), which is based on dynamic light-scattering techniques [ 18 ]. The encapsulation efficiency (EE, %) was also determined by estimating the encapsulation efficiency of phenolic compounds in MOLE as an indicator of prebiotic encapsulation and that of SCY cells as an indicator of probiotic encapsulation [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…There was the dissolution of endometrial tumor cell in endometrial cancer in a polymeric nanoparticle (NP) delivery system, which improves efficacy and safety of the combinatorial strategy [ 154 ] and also the development of a targeted drug delivery system for the uterus utilizing an immunoliposome platform targeting the oxytocin receptor leading to targeted liposomal drug delivery to the myometrium is reduced dose and reduced toxicity to both mother and fetus [ 155 ]. Likewise, Hassanein et al 2021 [ 156 ] reported the fabrication of Gonadotropin-releasing hormone (GnRH)–loaded–Chitosan Nanoparticles could allow a reduction in the conventional intramuscular GnRH dose used for AI in rabbits to half without affecting fertility. The combinatorial effect, poly(lactic-co-glycolic) acid nanoparticles loaded with epigallocatechin gallate(EGCG) and doxycycline (Dox) in a single vehicle appears to be promising for treating endometriosis.…”
Section: Application Of Nanotherapeutic In Reproductive Diseasesmentioning
confidence: 99%